Comparative analysis on the influence of land management on conservation methods of endangered species ranges - Buckmire, Sinder, author; Bombaci, Sara, advisor; Bailey, Larissa, committee member (Colorado State University. Libraries, 2025)
Species ranges play an important role in understanding species ecology for effective conservation management, with the distribution of endangered species ranges across different land management jurisdictions being a key determinant of the conservation strategies and regulatory frameworks that shape species recovery. This study used ArcGIS to perform spatial intersection analyses to quantify the overlap between federally-managed and Indigenous-managed lands, and the extant range of three species of high conservation concern (at least an Endangered listing under the IUCN Red List) in the US: the Black-footed Ferret, the Mojave Desert Tortoise, and the Western Alligator Snapping Turtle. Results found that the Black-footed Ferret and Mojave Desert Tortoise have a significantly larger portion of their total ranges on federally-managed lands, while the Western Alligator Snapping Turtle has a moderately balanced distribution across federal and Indigenous jurisdictions, but exhibits a much smaller amount of overlap with the two land management types across their total range. These patterns indicate that conservation methods for some endangered species depend on the strategies employed under a particular land management type, while others depend on collaborative governance. Overall, this study emphasizes the importance of integrating land governance into species range analyses, and highlights the need for collaborative Indigenous-federal conservation strategies to increase the effectiveness of conservation actions and improve recovery for species of high conservation concern.
Keywords: endangered species; conservation